Agricultural insurance: Policies and programs for reducing farmer risk - Ceballos, Francisco; Hazell, Peter B. R.; Hill, Ruth Vargas; Kramer, Berber (International Food Policy Research Institute, 2025)
Farm households face many market and production risks to their livelihoods, food security, and economic well-being. Agricultural insurance is intended to help protect households from risk, but many agricultural risks are difficult to insure against and demand for insurance products remains low. This chapter examines how policy-oriented research has encouraged public investment, facilitated farmer use, and improved farmer welfare, and explores how new technologies and approaches are creating opportunities for increasing coverage.